Rapid recognition of out-of-hospital cardiac arrest by emergency medical dispatchers is associated with improved survival. (25th November 2020) - Gnesin, F; Moeller, A.L; Mills, E.H.A; Zylyftari, N; Jensen, B; Boeggild, H; Ringgren, K.B; Kragholm, K; Lippert, F; Folke, F; Gislason, G; Torp-Pedersen, C.T
Abstract: Background: Emergency medical dispatchers' (EMD) recognition of out-of-hospital cardiac arrest (OHCA) is an essential part of the first link in the Chain of Survival. However, it is unknown whether the time-to-recognition of OHCA by EMD during an emergency call is associated with survival. Purpose: To investigate the effect of time-to-recognition on 30-day survival among patients with recognised OHCA. Methods: We linked data on OHCAs occurring in the Capital Region of Denmark from 2016 through 2017 to records of corresponding emergency calls. We defined recognition as dispatching an ambulance with an appropriate priority level and subsequently defined time-to-recognition as the time from start of the call to the time of dispatching the ambulance. Among patients with recognised OHCA, we performed uni- and multivariate logistic regression to investigate the association of time-to-recognition and 30-day survival and reported odds ratios (OR) with 95% confidence intervals (CI). Results: Among 2, 382 patients with OHCA, 94.2% were recognised, in which median age was 73.6 years, 61.6% were males and median time-to-recognition was 0.8 minutes (interquartile range 0.7 minutes). Patients for whom time-to-recognition was up to (but not including) one minute had more than three-fold higher probability of surviving 30 days (15.5%) compared to patients for whom time-to-recognition was three or more minutes (4.5%) (Figure 1). Time-to-recognition was significantly associated with 30-day survival: OR 0.75 per minute (95% CI 0.62–0.91, P<0.005), and results were similar in the adjusted analysis: OR 0.72 per minute (95% CI 0.58–0.90, P<0.005). Conclusion: Rapid recognition of OHCA by EMD resulted in improved survival rate of patients. This was particularly evident when time-to-recognition was three or more minutes. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Hjerteforeningen